A pomba-de-bando (Zenaida auriculata - aves, Columbidae) nas paisagens agrícolas do sudoeste do Brasil: distribuição, abundância e interações com a agricultura - Silva, Giliandro Gonçalves (2014)
Agriculture expansion and intensification reassemble bird communities, including the loss of species, reduced diversity and the population increase of some species able to use the novel resources available. In some circumstances these species may be perceived as overabundant and conflict with human activities. This dissertation examines 1) the influence of the land use in agricultural landscapes in the abundance of eared dove and 2) the recognition of eared dove's populations as overabundant in the Southwestern of Brazil. The study was conducted in grain-producing regions comprising the part of the States of Rio Grande do Sul, Santa Catarina, Paraná and São Paulo. We counted birds along 50 routes, each comprising 12 counting stations, placed on secondary roads and relate occurrence and abundance with land uses. We applied questionnaires to farmers record their perception about damages by eared doves in agriculture. Our data demonstrated that the eared dove was the most abundant species, representing 48% of total individuals counted and also one of the most common, being found in 93% of samples. At the landscape scale, the abundance of eared doves was associated positively with routes crossing landscapes dominated by plantations in winter and negatively associated with routes with large tracts of forests and mixed farming in summer. At the local scale the abundance of doves in winter was greater in routes with higher frequency of maize plantations and in summer in routes with higher frequency of sugar cane and soybean plantations. Thus, the type of land use influenced the abundance of doves. Of the farmers interviewed, 41% claimed some kind of damage to their crops. Among these, 70% reported damages of less than 10% of the planted area. The highest percentage of positive responses about damages occurred in Paraná, with 54% of complaints. Sixty seven percent of the reported damages were located up to 100 km from nesting colonies. The probability of reporting damages decreases 1% every 10 km away from a colony. We consider that eared doves can be classified as overabundant in parts of the States of Paraná and São Paulo, where the agricultural landscape favor high abundance of this species all over the year and risk of conflicts with agriculture is higher.